Konseling Kelompok untuk Meningkatkan Kepercayaan Diri Remaja Korban Kekerasan dalam Rumah Tangga (KDRT) - Marlina, Aisah (Persona:Jurnal Psikologi Indonesia, 2017)
This study aims to determine the effect of group counseling on increasing self-confidence in adolescent victims of domestic violence (domestic violence). The subjects in this study amounted to 5 teenagers consisting of 2 men and 3 women and joined in the 1 experimental group "One Group Pretest-Postes". The data collection tool used was the confidence scale, the data analysis method used was Wilcoxon signed ranks test. The results obtained by the significance value p = 0.042 (p <0.05) then the hypothesis is accepted and can mean that there is influence of group counseling on increasing self-confidence in adolescent victims of domestic violence.                Keywords: Group Counseling, Confidence